2009
DOI: 10.15421/010938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline stress on growth and crop yield of different maize (Zea mays) genotypes

Abstract: Effects of saline stress (NaCl) on yield and vegetative characteristics of eight maize cultivars were studied. The cultivars K3615/1, S.C704, B73, S.C302, Waxy, K3546/6, K3653/2, and Zaqatala were cultivated in two plots of the Astara region: one was with normal soil and the other – with salty one. Salinization reduced the plant height, ear length, ear diameter, number of plant leaves, stem diameter, number of rows in an ear, number of grains in a row, and dry plant mass in all cultivars. Maximal ear length wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Salt-stress stimulates an increase in growth inhibitors and a decrease in growth promoters, hence water disturbance in salt-stressed plants limits the uptake of water or absorption of the required nutrients (Khatoon et al 2010;Hala et al 2020). The reduction in fresh weight due to salt stress has been studied by numerous researchers and appeared as a common phenomenon in most trees and crop plants (Gurbanov and Molazem 2009;Alam et al 2016). In this study, a drastic reduction in shoot fresh weight (Figure 3b) was observed, which may be due to the disturbances in physiological activities under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Salt-stress stimulates an increase in growth inhibitors and a decrease in growth promoters, hence water disturbance in salt-stressed plants limits the uptake of water or absorption of the required nutrients (Khatoon et al 2010;Hala et al 2020). The reduction in fresh weight due to salt stress has been studied by numerous researchers and appeared as a common phenomenon in most trees and crop plants (Gurbanov and Molazem 2009;Alam et al 2016). In this study, a drastic reduction in shoot fresh weight (Figure 3b) was observed, which may be due to the disturbances in physiological activities under salt stress.…”
Section: Discussionmentioning
confidence: 99%